Edwardsiella piscicida type III protein EseJ suppresses apoptosis through down regulating type 1 fimbriae, which stimulate the cleavage of caspase‐8. (5th March 2020) - He, Tian Tian; Zhou, Ying; Liu, Ying Li; Li, Duan You; Nie, Pin; Li, Ai Hua; Xie, Hai Xia
Abstract: The type III secretion system effector EseJ plays a regulatory role inside bacteria. It suppresses the adherence of Edwardsiella piscicida ( E. piscicida ) to host epithelial cells by down regulating type 1 fimbriae. In this study, we observed that more macrophages infected with Δ eseJ strain of E. piscicida detached as compared with those infected with the wild‐type (WT) strain. Terminal deoxynucleotidyl transferase dUTP nick‐end labelling (TUNEL) staining and cleaved caspase‐3 examination revealed that the detachment is due to increased apoptosis, suggesting that EseJ suppresses macrophage apoptosis. However, apoptosis inhibition by EseJ is not relative to a type III secretion system (T3SS) and is not related to EseJ's translocation. Since EseJ negatively regulates type 1 fimbriae, murine J774A.1 cells were infected with Δ eseJ Δ fimA or Δ eseJ Δ fimH strains. It was demonstrated that Δ eseJ stimulates macrophage apoptosis through type 1 fimbriae. Moreover, we found that infecting J774A.1 cells with the Δ eseJ strain increased levels of cleaved caspase‐8, caspase‐9, and caspase‐3, demonstrating that EseJ inhibits apoptosis through either an extrinsic or a combination of extrinsic and intrinsic pathways. Pre‐treatment of macrophages with caspase‐8 inhibitor prior to infection with the Δ eseJ strain decreased the levels of cleaved caspase‐8, caspase‐9, and caspase‐3, indicating that the Δ eseJ strain stimulates apoptosis, mainly through an extrinsic pathway by up regulating type 1 fimbriae. Zebrafish larvae or blue gourami fish infected with the Δ eseJ strain consistently exhibited higher apoptosis than those infected with the E. piscicida WT strain or Δ eseJ Δ fimA strain. Taken together, we revealed that the T3SS protein EseJ of E. piscicida inhibits host apoptosis, mainly through an extrinsic pathway by down regulating type 1 fimbriae.